The Effectiveness of English Vlog Project Towards Students Speaking Ability at a Vocational High School - Brilian Siliwangi; Baiq Sumarni; Sugianto Sugianto (Universitas Pahlawan Tuanku Tambusai, 2026)
Speaking ability is one of the essential competencies in English as a Foreign Language (EFL), yet many Indonesian students continue to experience difficulties due to limited opportunities for authentic speaking practice and meaningful communication in classroom settings. Project-Based Learning (PjBL) has been widely recognized as an effective instructional approach because it engages students in authentic, collaborative, and learner-centered tasks that promote language use in real contexts. Therefore, this study aimed to investigate the effectiveness of the English Vlog Project, implemented through a Project-Based Learning approach, in improving students’ speaking ability. The study employed a pre-experimental one-group pretest–posttest design involving 19 tenth-grade students of class X DPIB at SMKN 6 Mataram selected through random sampling. Data were collected through classroom observation, speaking pretest, instructional treatment using the English Vlog Project, and posttest. Students’ speaking performance was assessed using Brown’s speaking rubric covering pronunciation, grammar, vocabulary, fluency, and comprehension. The data were analyzed using the Shapiro–Wilk normality test and a paired-samples t-test. The findings indicated that the data were normally distributed (Sig. = 0.133 0.05). Students’ mean speaking score improved from 60.32 in the pretest to 77.37 in the posttest, and the paired-samples t-test revealed a statistically significant difference between the two tests (Sig. = 0.001 0.05). These findings demonstrate that the English Vlog Project is an effective instructional strategy for enhancing students’ speaking ability in the EFL classroom.